1975
DOI: 10.1143/jjap.14.621
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Phase Epitaxial Growth of GaAs Crystals under a Mixed Gas Atmosphere

Abstract: Liquid phase epitaxial growth of GaAs crystals was performed under a mixed gas flow, a Pd-diffused H2 gas and an arsenic vapor. It is found that liquid phase epitaxy under a mixed gas flow is effective in preparing high quality GaAs epitaxial layers with nearly stoichiometric composition. By using a mixed gas atomosphere, the un-doped epitaxial layers with carrier concentrations of the order of 1012cm-3 and mobilties of 170,000cm2/V sec at 77K were obtained reproducibly. The concentration of deep impurity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1976
1976
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…The nature of the slope in N(x) versus W profiles can be explained firstly by the changing solubility of oxygen with temperature in the gallium melt. Ostubo [4] found that oxygen is more soluble in Ga at a lower growth temperature than at a higher growth temperature (ko = 5xl0 -5 at 800 to 725°C and ko == 6.5xl0 -4 at 700 to 625°C). Added to this is a decrease in As solubility in Ga with temperature decrease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the slope in N(x) versus W profiles can be explained firstly by the changing solubility of oxygen with temperature in the gallium melt. Ostubo [4] found that oxygen is more soluble in Ga at a lower growth temperature than at a higher growth temperature (ko = 5xl0 -5 at 800 to 725°C and ko == 6.5xl0 -4 at 700 to 625°C). Added to this is a decrease in As solubility in Ga with temperature decrease.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in summary, we note that the equilibrium state of equations (1) and (2) may be influenced by: (a) the rate of removal of Ga 2 O (v) , so that the Si production rate may be altered by changing the gas stream velocity or the furnace temperature, (b) controlled introduction of the oxygen species which can clamp Ga 2 O (v) production by holding equation (1) near steady state equilibrium so that Si production remains low. Further introduction of oxygen may even shift equation (1) to the left hand side so that no further Si is produced, (c) using an appropriate growth (bake-out) temperature regime: the distribution coefficient of oxygen and ultimately the donor concentration has been shown by Otsubo et al [4] to decrease linearly with increased bake-out temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…High-quality GaAs layers of considerable thickness can be obtained by this simple method with a simple process. 20,21) In this growth process, an Arsenic-saturated solution of Ga is prepared. As the solvent, 8 N Ga metal is used, and the polycrystalline GaAs is melted as the solute in this solution.…”
Section: Liquid Phase Epitaxial Growth Of High-quality Gaas Layermentioning
confidence: 99%
“…The Liquid Phase Epitaxy (LPE) is a method best to grow a thick and high-purity GaAs crystal. Using this method, the donor and acceptor impurity concentrations in the GaAs are decreased to 1013atoms/cm-3 [7][8][9][10]. It is nearly more than 100 times purer than the commercially available GaAs crystals containing the residual impurities concentration over 1015cm-3.…”
Section: Lpe Growth Of Gallium Arsenide For High Performance Detectorsmentioning
confidence: 99%